PENGARUH MODEL PROBLEM BASED FLIPPED CLASSROOM TERHADAP KEMAMPUAN BERPIKIR KRITIS IPA SD - Zakia Salsabila Akhzara; A.R Supriatna; Dudung Amir Soleh (JIPD (Jurnal Inovasi Pendidikan Dasar), 2023)
This study aims to determine the effect of the Problem Based Flipped Classroom learning model on critical thinking skills in learning grade V science at SDN Kebayoran Baru, South Jakarta. The research method used is an experiment with a two group post test only design. The samples in this study were 22 experimental class students and 22 control class students. The data analysis used to analyze the data from this study was the t test. Based on the results of the research data analysis, it can be concluded that there is a significant difference between the experimental class and the control class. This is evidenced by the results of the t test calculation obtained tcount of 5.31 while the t table is 1.68. Therefore, it can be concluded that it is greater than (5.32 > 1.68). This shows that (H0) is rejected and (H1) which states that there is a significant influence on the use of the problem-based flipped classroom learning model on the ability to think critically in science is accepted. Thus, the problem-based flipped classroom learning model has a positive influence on the critical thinking skills of science class V at SDN Kramat Pela 07, Kebayoran Baru, South Jakarta.